Using Flipgrid Discussions to Increase School Counseling Students’ Cultural Competence in the Online Classroom - Rebekah F Cole (Teaching and Supervision in Counseling, 2021)
This pre-test/post-test quasi-experimental design study investigated the use of Flipgrid to increase school counseling students’ cultural competence, which was measured by the Global Perspectives Inventory (GPI). Student participants in the experimental group utilized Flipgrid to engage in cultural discussions while participants in the control group utilized Blackboard discussion boards. An independent samples and paired-samples t-test were used to analyze the participants’ scores in the experimental and control groups. The statistically significant findings of the paired samples t-test suggest the effectiveness of utilizing Flipgrid in order to increase students’ cultural competence in the online learning environment. The study’s implications for teaching and research are discussed.
Keywords: Flipgrid; cultural competence; school counselor; discussion; online learning